Factors Influencing Central Lamina Cribrosa Depth: A Multicenter Study - Luo, Haomin; Yang, Hongli; Gardiner, Stuart K.; Hardin, Christy; Sharpe, Glen P.; Caprioli, Joseph; Demirel, Shaban; Girkin, Christopher A.; Liebmann, Jeffrey M.; Mardin, Christian Y.; Quigley, Harry A.; Scheuerle, Alexander F.; et al. (Investigative Ophthalmology & Visual Science, 2018)
Purpose: To quantify the influence of ocular and demographic factors on central laminar depth (LD) in healthy participants. Methods: A total of 362 normal subjects underwent optical coherence tomography (OCT) enhanced depth imaging of the optic nerve head (ONH) with a 24 radial B-scan pattern aligned to the fovea-to-Bruch's membrane opening (BMO) axis. BMO, anterior lamina, anterior scleral canal opening (ASCO), Bruch's membrane (BM), and the peripapillary scleral surface were manually segmented. The extent of laminar segmentation was quantified within 72 ASCO subsectors. Central LD was quantified relative to four reference planes: BMO, ASCO, BM, and scleral. The effects of age, sex, ethnicity, IOP, BMO area, ASCO area, and axial length on LD were assessed. Results: Laminar visibility was most consistent within the central ASCO (median 89%, range, 69%-95%). LDBMO and LDBM were significantly shallower in eyes with greater age, BMO area, and axial length and in females. LDASCO was shallower in eyes with greater ASCO area and axial length and in European and Hispanic descent compared to African descent eyes. LDSclera behaved similarly, but was not associated with axial length. BMO and ASCO area were not different between African descent and European descent eyes. Conclusions: Central LD was deeper in African descent eyes and influenced least by age, axial length, and sex, but more by ASCO area, when measured relative to the ASCO and sclera. However, the magnitude of these effects for all four reference planes was small, and their clinical importance in the detection of glaucoma and its progression remains to be determined.
EVALuna2:34750